Pengaruh Return on Asset, Return on Equity dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Sub Sektor Konstruksi Bangunan yang Terdaftar di BEI Periode 2019-2023 - Batuaji, Naga Fajar; Hendriyani, Rina Maria (Peneliti.net, 2025)
This study aims to determine and analyze the effect of return on asset, return on equity and earning per share on stock prices in building constructions sub-sector companies listed on the Indonesian Stock Exchange for the 2019-2023 period. The population in this study is a building constructions sub-sector company listed on IDX. Sampling using purposive sampling technique and obtained 5 companies as research samples. The observation period is 5 years, namely 2019-2023 so that it uses 25 company financial statements. This study uses the classical assumption test method, multiple linear regression analysis and hypothesis. Based on the regression results, it is known that silmutaneously ROA, ROE and EPS have an effect on the stock prices of building construction sub-sector companies listed on the IDX for 2019-2023 period. Partially, ROA and ROE has no effect on stock prices, while EPS has an effect on stock prices of building construction sub-sector companies listed on the IDX for the 2019-2023 period.